Multiterminal source coding problem with several side informations at the decoder - Oohama, Y. (2008 IEEE International Symposium on Information Theory, 2008)
In this paper we consider the separate coding problem for L + 1 correlated memoryless sources. We deal with the case where L sources work as partial side information at the decoder for the reconstruction of the remaining source. The determination problem of the rate-distortion region for this system is the so called many-help-one problem and has been known as a highly challenging problem for almost thirty years. We survey previous results on this problem. Through survey we discuss some implication of the many-help-one problem for the progress of multiterminal rate-distortion theory.